2017
DOI: 10.1002/lsm.22700
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multi‐wavelength laser irradiation of enamel and dentin surfaces at 0.355, 2.94, and 9.4 μm on surface morphology, permeability, and acid resistance

Abstract: Objective Ultraviolet (UV) and infrared (IR) lasers can be used to specifically target protein, water, and mineral, respectively, in dental hard tissues to produce varying changes in surface morphology, permeability, reflectivity and acid resistance. The purpose of this study was to explore the influence of laser irradiation and topical fluoride application on the surface morphology, permeability, reflectivity, and acid resistance of enamel and dentin to shed light on the mechanism of interaction and develop m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Enamel ablation by femtosecond lasers has been demonstrated by several authors (Chen et al, 2015; Chen et al, 2016; Le, Bertrand, & Vilar, 2016; Loganathan, Santhanakrishnan, Bathe, & Arunachalam, 2021; Yuan, Zheng, Sun, Wang, & Lyu, 2017). Nevertheless, there is no detailed characterization of femtosecond laser‐irradiated surfaces using subablative parameters, since previous studies have demonstrated the ability of high‐power lasers with subablative parameters to make dental enamel more acid‐resistant (Behroozibakhsh et al, 2018; Chang et al, 2017). The role of laser irradiation in caries prevention has been widely studied with a focus on the increase of caries resistance caused by a decrease in the enamel demineralization rate (Geraldo‐Martins et al, 2013; Tavares et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enamel ablation by femtosecond lasers has been demonstrated by several authors (Chen et al, 2015; Chen et al, 2016; Le, Bertrand, & Vilar, 2016; Loganathan, Santhanakrishnan, Bathe, & Arunachalam, 2021; Yuan, Zheng, Sun, Wang, & Lyu, 2017). Nevertheless, there is no detailed characterization of femtosecond laser‐irradiated surfaces using subablative parameters, since previous studies have demonstrated the ability of high‐power lasers with subablative parameters to make dental enamel more acid‐resistant (Behroozibakhsh et al, 2018; Chang et al, 2017). The role of laser irradiation in caries prevention has been widely studied with a focus on the increase of caries resistance caused by a decrease in the enamel demineralization rate (Geraldo‐Martins et al, 2013; Tavares et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difficulty of controlling the enamel demineralization processes, new technologies have been studied, such as the use of irradiation with high‐intensity lasers, which have been used in dental enamel with subablative parameters for the prevention and control of caries lesions (Fornaini, Brulat, Milia, Rockl, & Rocca, 2014). When used for preventive purposes, the irradiation of dental enamel with CO 2 , Er,Cr:YSGG, Er:YAG and Nd:YAG lasers modifies the enamel morphology and physical properties, including melting, recrystallization, and melting of hydroxyapatite crystals (Fornaini et al, 2014; Chang et al, 2017; Geraldo‐Martins, Lepri, & Palma‐Dibb, 2013; Tavares, de Eduardo, Burnett Jr, Boff, & de Freitas, 2012). The objective of modifying the chemical and crystalline structure of dental enamel is to favor the stabilization of calcium and phosphate ions by significantly reducing the content of intercrystalline organic material, water, and carbonate, increasing tissue resistance to demineralization (Corrêa‐Afonso, Bachmann, Almeida, Corona, & Borsatto, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that laser treatment can work synergistically with the application of topical fluoride to further enhance its inhibitory effect [11,21]. Many studies have shown the effect of treatment combining irradiation by carbon dioxide laser at different wavelengths and topical fluoride application on inhibiting tooth demineralization [17,[22][23][24][25][26][27]. A study demonstrated that the combined use of a CO 2 laser and sodium fluoride can significantly increase the uptake of fluoride ions [28].…”
Section: Introductionmentioning
confidence: 99%
“…10 This process decreases the permeability and hampers the acid diffusion, thereby reducing enamel demineralization. [11][12][13] Some CO2 parameters, such as output power 14,15 and a wavelength of 10.6 um 3,12, [16][17][18] have been widely studied to prevent demineralization or increase enamel microhardness. However, different pulse emission modes of the CO 2 laser have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%